Views of breast cancer survivors on work participation guidance by general practitioners: a qualitative study - Marie-Christine Sarfo; Kristel M. van Asselt; Monique H. Frings-Dresen; Femke de Jong; Nynke van Dijk; Angela G. E. M. de Boer (BMC Primary Care, 2022)
Abstract Background Breast cancer survivors can be at high risk of having work-related problems. Previous studies suggest that GPs could discuss work participation with cancer patients and provide guidance. The aim this study is to explore the experiences and expectations of breast cancer survivors with their GPs’ role regarding guidance on work participation and return to work. Methods A qualitative study with Dutch female breast cancer survivors was held in the Netherlands. Four focus groups with 25 participants were conducted and audio-taped. Transcripts were analysed using thematic analysis. Results Breast cancer survivors reported a wide range of experiences with guidance from their GPs regarding work participation. Patients who contacted their GPs with work-related issues felt listened to during the consultation. Some patients experienced very limited or no guidance, while others were intensively guided by their GPs. The guidance was provided in the form of counseling, psychosocial support, and referral to other health care professionals. When cancer patients experienced problems with reintegration in work, they expected GPs to have a supportive and referring role in work participation guidance. Conclusion In returning to work, breast cancer survivors expect their GPs to play a supportive role, especially when they encounter difficulties in reintegrating. However, their actual experience of guidance received from their GPs varied, from none received at all, to intensive support provided.